Intramolecular Alkene Hydroamination with Hybrid Catalysts Consisting of a Metal Salt and a Neutral Organic Base - Stegner, Philipp; Fischer, Christian; Nguyen, D. Thao; Rösch, Andreas; Penafiel, Johanne; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
Hybrid catalysts consisting of alkaline earth iodides (AeI2) and the Schwesinger base tBuP4 catalyse the intramolecular alkene hydroamination of H2C=CHCH2CR2CH2NH2 [CR2=CPh2, C(CH2)5, CMe2]. Activities decrease along the row: Ca > Sr >> Mg > Ba. Hybrid catalysts consisting of tBuP4 and ZnI2, AlI3, FeCI3 or NaI were found to be fully inactive. Also, the hybrid catalyst tBuP3/CaI2 was not active which means that the base strength of the non-nucleophilic organic base must be higher than that of tBuP3 (pKa BH+ = 38.6). Combinations of tBuP4 with CaX2 (X = Cl, Br, OiPr, OTf, NTf2) were found to be fully inactive which may in part be explained by poor solubility. The hybrid catalysis method is therefore limited to the combination tBuP4/CaI2 but the iodide ligands may be partially or fully replaced by chiral ligands. Chiral modifications of the hybrid catalysts gave in intramolecular alkene hydroamination ee values up to 33 %.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Calcium; Homogeneous catalysis; Intramolecular alkene hydroamination; Schwesinger bases

Lewis acidic alkaline earth metal complexes with a perfluorinated diphenylamide ligand - Fischer, Christian; Rösch, Andreas; Elsen, Holger; Ballmann, Gerd; Wiesinger, Michael; Langer, Jens; Färber, Christian; Harder, Sjoerd (Dalton Transactions, 2019)
Alkaline earth metal (Ae) chemistry with the anion [N(C 6 F 5 ) 2 ] - has been explored. Deprotonation of the amine (C 6 F 5 ) 2 NH, abbreviated in here as N F H, with 0.5 equivalent of AeN′′ 2 (N′′ = N(SiMe 3 ) 2 ) is fast and gave, dependent on the solvent, the complexes AeN F 2 , AeN F 2 ·(THF) 2 and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca, Sr). Using a 1/1 ratio, mixed amide complexes were obtained: N F AeN′′ (Ae = Mg, Ca, Sr). Crystal structures of the monomers AeN F 2 ·(THF) 2 (Ae = Mg, Ca, Sr) and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca) are presented and compared with those of AeN′′ 2 ·(THF) 2 . In addition, crystal structures of the homoleptic dimer (MgN F 2 ) 2 and the heteroleptic dimers (N F AeN′′) 2 (Ae = Mg, Ca, Sr) are discussed. All structures are strongly influenced by very short Ae⋯F contacts down to circa 2.11 Å (Mg), 2.50 Å (Ca) and 2.73 Å (Sr). AIM analysis illustrates that, although Ae⋯F contacts are short, there is no bond-critical-point along this axis, indicating an essentially electrostatic interaction. The monomeric complexes feature strong C 6 F 5 ⋯C 6 F 5 π-stacking, resulting in unusually acute N F -Ae-N F angles as small as 95°. Heteroleptic (N F AeN′′) 2 complexes retain their dimeric structure in C 6 D 6 solution and there is no indication of ligand scrambling by the Schlenk equilibrium, suggesting that an electron withdrawing ligand may stabilize heteroleptic complexes. According to DFT calculations, the heteroleptic arrangement is 70 kJ mol -1 more stable than the homoleptic dimers. The Lewis acidity of MgN F 2 has been quantified with the Gutmann-Beckett method and by calculation of the Fluoride-Ion-Affinity. The latter calculations show that the Lewis acidity of MgN F 2 and CaN F 2 is comparable to that of B(C 6 F 5 ) 3 . Dimeric (MgN F 2 ) 2 fully abstracts Et 3 PO from Et 3 PO·B(C 6 F 5 ) 3 and may have potential in Lewis acid catalysis.
CRIS-Team Scopus Importer:2019-06-04